“If I were Anne”: how Sweden brought Anne of Green Gables to the Palestinian classroom - McDonald-Rissanen, Mary (SOLETRAS, 2014)
Sweden’s teachers have a history of engaging children through literature into the humanistic endeavor of developing self-esteem and a positive attitude to life. The Canadian classic Anne of Green Gables written by Lucy Maud Montgomery in 1908 is one of the worksof literature where a pedagogy has been developed to further these aims. The Swedish organization Diakonia has been instrumental in promoting these same ideals of empowering children through literature. While in Palestine I became familiar with Diakonia’s activities with local educators and in this article I examine how Palestinian teachers use this methodology with their Arabic copy of Anne of Green Gables.